Conditioned medium from mesenchymal stem cells improves condylar resorption induced by mandibular distraction osteogenesis in a rat model. Issue 3 (March 2021) - Katagiri, Wataru; Endo, Satoshi; Takeuchi, Ryoko; Suda, Daisuke; Saito, Naoaki; Kobayashi, Tadaharu
Abstract: Condylar resorption (CR) after surgical orthognathic treatment is defined as dysfunctional remodeling of the temporomandibular joint manifested by morphological changes with decreased condylar head volume that cause occlusal and esthetic changes. Although both conservative and surgical treatment strategies have been employed for the treatment of CR, effective procedures have not been established till date. In this study, the effects of MSC-CM on CR were investigated. Bone marrow-derived MSCs of rats (rMSCs) were cultured until 80% confluent, cultured in serum-free conditioned medium for 48 h; the collected medium was defined as MSC-CM. Osteogenesis, chondrogenesis, and angiogenesis-related gene expression in rMSCs cultured with MSC-CM was evaluated by quantitative real-time polymerase chain reaction. A rat CR model was used for animal studies, in which CR occurred after mandibular distraction osteogenesis for 10 days. MSC-CM was injected via the tail vein and quantitative and qualitative evaluations were performed by micro-computed tomography (micro-CT) and histology. MSC-CM enhanced osteogenesis-, chondrogenesis-, and angiogenesis-related gene expression in rMSCs. Micro-CT showed CR in control groups; however, it was observed to be improved in the MSC-CM group. Histologically, an enlarged cartilage layer was seen in the MSC-CM group, while cartilage layers had almost thinned or disappeared in control groups. These results indicate that MSC-CM improved CR. Abstract : condylar resorption, orthognathic surgery, mesenchymal stem cells, secretome, conditioned media, regenerative therapy